Anti-inflammatory effects of NaB and NaPc in Acinetobacter baumannii-stimulated THP-1 cells via TLR-2/NF-κB/ROS/NLRP3 pathway - Shu Chen; Yan-Yan Zhang; Hai Zhang; Long-Kun Ding; Yue Xi; Man Yan; Chang Sun; Liang Wu; Hao Hu (Acta Pharmaceutica)
This study evaluated the anti-inflammation effect of the three main short-chain fatty acids (SCFAs) on Acinetobacter baumannii-induced THP-1 cells. The three main SCFAs could inhibit A. baumannii-stimulated THP-1 cell NF-κB pathway activity and the expressions of NLRP3 inflamma-some and GSDMD, and increase autophagy. The three main SCFAs, especially the sodium butyrate (NaB), had the effect of down-regulation of ROS and TLR-2 expression in THP-1 cells. NaB and sodium propionate (NaPc), but not sodium acetate (NaAc), dramatically suppressed IL-1β and IFN-γ expression. The results indicated that NaB and NaPc could significantly inhibit the inflammation of THP-1 cells induced by A. baumannii, and the inhibitory effect was in the order of NaB > NaPc > NaAC. NaB and NaPc may inhibit inflammation through TLR-2/NF-κB/ROS/NLRP3 signaling pathway.